LEVEL OF TOURIST SATISFACTION WITH TANJUNG SIAMBANG BEACH, DOMPAK ISLAND, TANJUNGPINANG CITY - Haidawati Haidawati; Khairunnisa Khairunnisa; Budiyanto Budiyanto (Politeknik Kelautan dan Perikanan Dumai, 2023)
Dompak Island, Tanjungpinang City has a potential beach tourism object. The beauty of the beach is the main attraction for tourists. There are several beach tours on Dompak Island, one of which is Tanjung Siambang Beach. Through the Tourism and Culture Office of Tanjungpinang City, tourism industry stakeholders and Tanjungpinang City have worked to manage tourist objects, increase tourist visits and develop attractions at Tanjung Siambang Beach. Tourist satisfaction greatly influences the increase in visits to a tourist attraction. The research aims to determine the level of tourist satisfaction with the Tanjung Siambang Beach tourist attraction using a quantitative descriptive method. Analysis of research data using Customer Satisfaction Index Analysis (CSI) and Importance Performance Analysis (IPA). The results showed that tourists were quite satisfied with the Tanjung Siambang Beach tourist attraction with a CSI value of 57.53% and an average conformity level obtained of 57.94% which shows an overall picture that the performance of Tanjung Siambang Beach has not been able to meet visitor expectations because the value Conformity level is still below 100% and not optimal.